Bioactive compounds with antifungal activity against pathogens isolated from pregnant woman: Gallesia integrifolia (garlic wood) is a promising treatment for vulvovaginal candidiasis. (15th September 2022) - de Souza, Amanda Nascimento Vasques; Faria, Maria Graciela Iecher; da Rocha, Cristiane Edna; Philippsen, Gisele Strieder; Silva, Gabriela Catuzo Canonico; da Silva, Gustavo Ratti; Inumaro, Rodrigo Sadao; Gonçalves, José Eduardo; Gazim, Zilda Cristiani; Wietzikoski, Samantha; Lívero, Francislaine Aparecida dos Reis; Seixas, Flavio Augusto Vicente; et al.
Abstract: Ethnopharmacological relevance: The leaves, bark, and roots of Gallesia integrifolia are consumed in folk medicine through infusion, decoction, and topical preparation by crushing because of its pharmacological properties in several peripheral system disorders, including microbial infections. The presence of various molecules in different parts of the plant likely confers this species' fungicidal action, but scientific evidence is lacking. Vulvovaginal candidiasis mainly affects women of reproductive age. When left untreated, it can cause pregnancy complications. Currently available antifungals often cause undesirable side effects. New alternative therapeutic strategies based on medicinal plants have been proposed. Aim: To investigate the antifungal activity of G. integrifolia against vulvovaginal candidiasis secretion in pregnant women. Materials and methods: Antifungal activity was determined by the minimum inhibitory concentration (MIC), determined by broth microdilution method using Candida spp (NEWP1210), C. albicans (CCCD-CC001), C. tropicalis (CCCD-CC002) standard and clinical isolates from pregnant women with vulvovaginal candidiasis. Nystatin and fluconazole were used as positive controls. The chemical composition of essential oils that were extracted from leaves, flowers, and fruits of G. integrifolia was determined by gas chromatography coupled to mass spectrometry. Reverse docking was used to suggest a possible target in Candida . Conventional docking was used to identify the most probable compound that inhibits fungal growth. Results: A total of 24 compounds were identified, accounting for ∼99% of volatile constituents in the essential oils. Leaves of G. integrifolia contained 3, 5-dithiahexanol-5, 5-dioxide (40.93%), flowers contained methionine ethyl ester (46.78%), and fruits contained 2, 8-dithianonane (54.01%) as the most abundant compounds. The MICs of essential oils of leaves, flowers, and fruits of G. integrifolia against standard strains of Candida spp, C. albicans, and C. tropicalis ranged from 13.01 to 625.00 μg/mL. The essential oil of flowers more effectively inhibited Candida spp. Essential oils of leaves and flowers were similar to fluconazole against C. albicans . Essential oils of flowers and fruits were similar to fluconazole against C. tropocalis . In Candida yeast species that were isolated from vaginal secretion samples from pregnant patients, the MICs of leaves and flowers ranged from 52.08 to 5000.00 μg/mL. The essential oil of leaves (277.77 μg/mL) was the most active against C. albicans . No significant differences were found between the essential oils of leaves and flowers against C. glabrata . Docking simulations suggested that phytol in leaves and flowers was responsible for the antimicrobial effect. Conclusion: The present results suggest the potential therapeutic use of G. integrifolia, especially its leaves and flowers, against Candida and vulvovaginal candidiasis. Graphical abstract: Image 1 Highlights: Gallesia integrifolia  are consumed in folk medicine through infusion, decoction, and topical preparation for several disorders including microbial infections. We evaluated the antifungal activity of G. integrifolia against vulvovaginal candidiasis secretion in pregnant women. Bioactive compounds of  G. integrifolia  presented antifungal activity against standard strains and  Candida  yeast species isolated from cultures of vaginal secretions from pregnancy women. Leaves were more efficient against C. albicans, and flowers were more efficient against C. glabrata. Docking simulations suggested that phytol in leaves and flowers was responsible for the antimicrobial effect.